Fungal flora of Southeastern Wisconsin - (:unkn) unknown (My University, 1984)
Since its reorganization in 1981, one goal of the Wisconsin Mycological Society has been a comprehensive long-term survey of fleshy and other fungi of southeastern Wisconsin. Over a period of years, random collections are to be made at a series of selected foray sites to document spring through fall floras. The UWM Field Station is one of these foray sites. Habitat and locality are to be recorded for each specimen along with field characteristics. Each identified collection will be dried and filed in the herbarium of the Milwaukee Public Museum. To date 35 specimens representing 29 species are on file. These were gleaned from two brief trips into the mesic beech-maple forest and one into Cedarburg Bog. The ephemeral nature of most fungal macrocarps and the fluctuations in yearly precipitation (hence patterns of fruiting) will necessitate numerous future visits before a comprehensive survey of the station mycof10ra can be completed.
Keywords: fungi; UWM Field Station